Feminist approaches to art therapy - Hogan, Susan, 1961- (Routledge, 1997)
A comprehensive survey of women's issues within art therapy. Leading international practitioners discuss topics such as assertiveness, empowerment, sexuality and childbirth, as well as issues around class, race and age.